Does the Female Labor Market Exhibit Name Effects? Evidence from China. - Jiang, Changliu; Ning, Yi (Women's Studies, 2025)
The article presents evidence from China showing the name effects of the female labor market. Topics discussed include Chinese naming customs and their impact on careers, socio-psychological functions of names within Chinese culture, relationship between name characteristics and occupational development, the interplay between gender, culture and societal expectations in career progressions, promotion of workplace gender equality and enhancement of occupational achievements of women.